VAT pass-through and competition: Evidence from the Greek islands - Lydia Dimitrakopoulou; Christos Genakos; Themistoklis Kampouris; Stella Papadokonstantaki (Deutsches Institut für Wirtschaftsforschung (DIW), 2023)
We examine how competition affects VAT pass-through in isolated oligopolistic markets as defined by the Greek islands. Using daily gasoline prices and a difference-in-differences methodology, we investigate how changes in VAT rates are passed through to consumers in islands with different market structure. We show that pass-through increases with competition, going from 50% in monopoly to around 80% in more competitive markets, but remains incomplete. We also discover a rapid rate of adjustment for VAT changes, as well as a positive relationship between competition and the rate of price adjustment. Finally, we document higher pass-through for products with more inelastic demand.
Keywords: H22; L1; 330; Pass-through; Tax incidence; Gasoline; Value added tax (VAT); Market structure; Competition; Greek islands